The origin of present day musical taste in Nigeria - Lane, Michael G. M. (International Library of African Music, 1956)
In considering the music of Nigeria, its future and its past, it is essential that an appreciation of its cultural environment and evolution is taken into account, the present day trends and tastes being a direct reflection of traditional modes. The African population of Nigeria is divided into numerous tribes, speaking different languages, worshipping various Gods and differing completely from one another in manners and customs.
Keywords: Music appreciation; Music; Ethnomusicology; Foreign Influences; Nigeria; African Music